Response of Indian mustard (Brassica juncea) and blackgram (Phaseolus mungo) grown in rotation to sulphur fertilization in acid soil - SINGH, SURENDRA; SINGH, K P; SARKAR, A K; SINGH, S K (The Indian Journal of Agricultural Sciences, 2013)
A 2-year-field experiment was conducted on response of Indian mustard (Brassica juncea L.) and blackgram (Phaseoius mungo Roxb.) grown in rotation to sulphur application in acid red loam soils of Bihar plateau revealed an increase in grain yields, crop uptake of sulphur, protein and oil yield of seeds due to application of 60-80 kg S/ha as phospho gypsum or pyrites. Application of 60 kg S/ha increased the grain yield of mustard by 320 kg/ha over the control. The’residual effect of 80 kg S/ha was significant in increasing the yield of black gram grain by 200 kg/ha over control. Phospho gypsum as a source of S was superior to pyrites in Indian mustard due to its sulphate sulphur content. Low grade pyrites, on the other hand, showed high residual effect on blackgram. Sulphur application resulted in a linear increase in oil content of mustard and protein content of black gram up to 80 kg S/ha level. Results suggest the need to sulphur application in soils low in available sulphur to boost crop yields and increase oil and protein content of oil seeds and pulses, respectively.